Detecting human presence at the border of the Northeastern Italian Pre-Alps. 14C dating at Rio Secco cave as expression of the first Gravettian and the late mousterian in the Northern Adriatic Region. - Sahra Talamo; Marco Peresani; Matteo Romandini; Rossella Duches; Camille Jéquier; Nicola Nannini; Andreas Pastoors; Andrea Picin; Manuel Vaquero; Gerd-Christian Weniger; Jean-Jacques Hublin (PLoS ONE)
In the northern Adriatic regions, which include the Venetian region and the Dalmatian coast, late Neanderthal settlements are recorded in few sites and even more ephemeral are remains of the Mid-Upper Palaeolithic occupations. A contribution to reconstruct the human presence during this time range has been produced from a recently investigated cave, Rio Secco, located in the northern Adriatic region at the foot of the Carnic Pre-Alps. Chronometric data make Rio Secco a key site in the context of recording occupation by late Neanderthals and regarding the diffusion of the Mid-Upper Palaeolithic culture in a particular district at the border of the alpine region. As for the Gravettian, its diffusion in Italy is a subject of on-going research and the aim of this paper is to provide new information on the timing of this process in Italy. In the southern end of the Peninsula the first occupation dates to around 28,000 14C BP, whereas our results on Gravettian layer range from 29,390 to 28,995 14C years BP. At the present state of knowledge, the emergence of the Gravettian in eastern Italy is contemporaneous with several sites in Central Europe and the chronological dates support the hypothesis that the Swabian Gravettian probably dispersed from eastern Austria.